Perlindungan Hewan Sebagai Bagian dari Hak Asasi Lingkungan: Perspektif Hukum Indonesia - Komang Ratih Ayu Maheswari; I Gusti Putu Yusmira Devi Yani; Komang Jaqueena Mahaputri Malka (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This article was written due to the lack of animal protection in Indonesia, evidenced by numerous cases of animal abuse perpetrated by the public. This research aims to broaden our understanding of the importance of animal protection and welfare. The method used is literature analysis, which involves reading and comparing various journals on animal protection law. The analysis was conducted by identifying key issues, trends, and recommendations put forward by researchers.